SISTEM INFORMASI PENJUALAN SOUND KAROKE MENGGUNAKAN PENGAPLIKASIAN BAHASA JAVA - Hanif Estu Saputra; Dendy Kurniawan (LPPM Politeknik Pratama Kendal, 2022)
The city of Semarang has a fairly large business opportunity to sell avino sound karaoke. To see business opportunities selling avino sound karaoke, it is necessary to do a business feasibility analysis. Business feasibility analysis is reviewed from market, technical, human resource management, legal, and financial aspects. Audio sound sales business is declared feasible based on 5 aspects. Based on the financial aspect analysis, the payback period is 4 years and 7 months, the NPV is Rp. 4,997,087,407 and the IRR value of 40.77% is greater than the MARR of 11.77% for the capacity to sell hundreds of units of various types of products. Based on the sensitivity analysis results, the sales of avino sound karaoke is still feasible if there is no decrease in the number of requests and selling prices of more than 19.17%, and an increase in investment of more than 29.5%.